A Universal Force Field for Materials, Periodic GFN-FF: Implementation and Examination - Gale, Julian; Leblanc, L.M.; Spackman, Peter; Silvestri, A.; Raiteri, Paolo (AMER CHEMICAL SOC, 2021)
In this study, the adaption of the recently published molecular GFN-FF for periodic boundary conditions (pGFN-FF) is described through the use of neighbor lists combined with appropriate charge sums to handle any dimensionality from 1D polymers to 2D surfaces and 3D solids. Numerical integration over the Brillouin zone for the calculation of πbond orders of periodic fragments is also included. Aside from adapting the GFN-FF method to handle periodicity, improvements to the method are proposed in regard to the calculation of topological charges through the inclusion of a screened Coulomb term that leads to more physical charges and avoids a number of pathological cases. Short-range damping of three-body dispersion is also included to avoid collapse of some structures. Analytic second derivatives are also formulated with respect to both Cartesian and strain variables, including prescreening of terms to accelerate the dispersion/coordination number contribution to the Hessian. The modified pGFN-FF scheme is then applied to a wide range of different materials in order to examine how well this universal model performs.